IMPROVING VTE RISK ASSESSMENT IN HOSPITALISED PATIENTS IN A TERTIARY CARE HOSPITAL IN IRELAND - Muhammad Irfan Khan; Aisling O’Brien; Catriona O’Leary; Virginia Silvari; Cleona Duggan; Susan O’Shea (Journal of Ayub Medical College Abbottabad, 2024)
Background: The initial baseline audit showed that only 24% of patients had a documented VTE- RA, this demonstrated an urgent need to improve VTE-RA in hospitalised patients. This quality improvement project (QIP) aimed to achieve 90% compliance in completing the VTE-RA tool and embedding this process into practice. Several measures were carried out which included the development of a TP policy, VTE-RA tool, education sessions and monthly point prevalence audits incorporating Plan, Do, Study, Act (PDSA) cycles. A follow-up audit was conducted one-year post-implementation using the same methodology as the baseline. Methods: This was a single centre before-after study, using a prospective cross-sectional design for both the baseline and post-intervention studies in a tertiary referral hospital in Cork, Ireland. All adult inpatients (>18 years) were eligible for inclusion. Documented evidence of VTE-RA and a prescription of TP were recorded. Results: The follow-up audit showed significant (p <0.001) improvement in documentation of VTE-RA from 24% (244/1019) to 57% (612/1070) and the prescription of pharmacological TP increased significantly (p<0.001) from 43% (441/1019) to 67% (713/1070). This improvement in VTE-RA was highest in patients with an increased risk of thrombosis from 21.9% (n=180/819) to 61% (n=493/807). Conclusion: The introduction of a TP policy and VTE-RA tool increased compliance by 33%. However, without a dedicated multidisciplinary thrombosis team to actively implement this, the achievements to date are unsustainable and attaining 90% compliance with VTE-RA is unlikely.